KUALITAS PELAYANAN IZIN MENDIRIKAN BANGUNAN PADA BADAN PENANAMAN MODAL DAN PELAYANAN PERIZINAN TERPADU KABUPATEN SIGI - Nasrun, Nasrun (Katalogis, 2016)
This study aimed to determine the quality of building permit services on the Sigi Regency Board of Investment and Integrated Licensing Services. This study used qualitative method. The research location was the Office of Sigi Regency Board of Investment and Integrated Licensing Services. Informants were selected using purposive sampling, i.e. the technique of determining informants with certain considerations by setting 7 (seven) informants. Data were collected through observations, interviews, and documentations. The theory used in this study was the theory of Zethmal, Parasuraman and Berry, consisting of 5 (five) dimensions: tangibles, reliability, responsiveness, assurance, and empathy.Based on the research results, it could be concluded that the quality of building permit services at Sigi Regency Board of Investment and Integrated Licensing Services had not been going well. First, tangibles dimension: the facilities and infrastructures of the Office were not adequate, the lounge area which must be addressed, and the toilets needed to be added; despite the Office status was only something owed. However, the apparatus neatness had been good. Second, reliability dimension: the quickness of the apparatus in providing services was not in accordance with the people’s expectations because there was no independence in the licensing process and the authority was still in the technical departments. Third, responsiveness dimension: the apparatus who had been serving the applicants had been good, but the quickness in completing the issuance of licenses was not maximized because there was no Standard Operational Procedures. Fourth, assurance dimension: the guarantee given by the apparatus to applicants had not been timely because of the delay in the process at the technical services. Fifth, emphaty dimensions: the services provided by the apparatus of the Board were not discriminatory and always be polite and courteous.